Dampak Aktivitas Penambangan Pasir Terhadap Tingkat Keanekaragaman Spesies Perairan di Sungai Cibanjaran Kecamatan Sukaratu Kabupaten Tasikmalaya - Fauzan, Mochamad Miftah; Nugraha, Setya Hafizh; Tiyasa, Muhammad Wijdan; Ridho, Tanto Muhammad; RS, Esta Rendra (Symbiotic: Journal of Biological Education and Science, 2025)
The slopes of Mount Galunggung, particularly in Sukaratu District, Tasikmalaya Regency, have long been a major site for sand mining activities since the 1984 eruption. Open-pit mining, especially along the Cibanjaran River, has led to changes in water quality due to sedimentation and pollution from the sand washing process. This study aims to analyze the impact of sand mining on aquatic species diversity in the Cibanjaran River. Data were collected from three observation stations with varying exposure to mining activities, along with measurements of physical parameters such as temperature, pH, and water discharge. The results showed that species diversity was very low at the station closest to the mining site (H’ = 0) and increased at stations further downstream (H’ = 1.731 and H’ = 1.345). These findings indicate that sand mining significantly affects aquatic biodiversity. Sustainable environmental management is crucial to protect the river ecosystem.